Competition and Profitability in European Financial Services - Balling, Morten (Routledge International Studies in Money and Banking, 2006)
Financial services firms play a key role in the European economy. The efficiency and profitability of these firms and the competition among them have an impact on allocation of savings, financing of investment, economic growth, the stability of the financial system and the transmission of monetary policy. This collection of research contributions includes evaluations of trends in the European financial service industry and examinations of the driving forces of efficiency, competition and profitability of financial firms and institutions in Europe. The papers have been written by leading academics and researchers in the field, who specialize in strategic, systematic and policy issues related to the European financial services industry. This edited collection will be will be essential reading for students and academics but will also be of interest to financial practitioners and government officials interested in acquiring a deeper understanding of this complex issue.